Peningkatan Kompetensi Masyarakat Berbasis Sapta Pesona Melalui Service Excellent Di Perkampungan Budaya Betawi Setu Babakam - Liliana Dewi; Subur Karyatun; Reza Emelia (Masyarakat Pariwisata : Journal of Community Services in Tourism, 2022)
Perkampungan Budaya Betawi Setu Babakan is a community Betawi cultural preservation centre. Research problems are communities lack of socialization, and training about destination tourism management impacted service excellence and environment. The objective of this community service on Perkampungan budaya Betawi Setu Babakan is to share knowledge with communities to develop human resources tourism competencies and give service excellence. Participants are local communities and local government, UPK Setu Babakan. The result is that the locals get knowledge and experience about Sapta Pesona and how to serve excellent visitors.